THE CONTRAVENTIONAL LIABILITY UNDER LAW NO. 8/1996 ON COPYRIGHT AND RELATED RIGHTS, REPUBLISHED, WITH SUBSEQUENT AMENDMENTS AND ADDITIONS - Iacob-Cătălin MARCU (Challenges of the Knowledge Society, 2025)
The present study addresses the issue of the contraventional liability as a consequence of committing any of the acts provided for in art. 190 and 191 of Law no. 8/1996 on copyright and related rights, republished, with subsequent amendments and additions, from the perspective of analyzing certain aspects of the respective contraventions, such as, in particular the active subject of these contraventions and the material element of the objective side of the same contraventions, including the special requirement of that element, as well as from the perspective of the general procedural aspects of the respective contraventions, taking into account the relevant specialized literature. At the same time, the present study contains elements of the Romanian jurisprudence and the CJEU jurisprudence on the matter examined, including some aspects that have been settled differently by Romanian courts. This study also includes some critical observations by the author on the flawed manner in which the contraventions analyzed were regulated, including with regard to compliance with the requirements of clarity and predictability of the rules governing them, which may lead to inconsistent practices, both in the administrative and judicial phases of the contraventional procedure, aspects in consideration of which appropriate de lege ferenda proposals have been formulated.